A Static or Dynamic Union: Euroscepticism and the Internal Legitimacy of the European Integration - Petr Kaniok (Czech Journal of International Relations, 2011)
The article focuses on the role of the phenomenon of Euroscepticism in the issue of the legitimacy of the European Union (EU), namely on the relation between the current conceptualisation of Euroscepticism and the EU’s ability to operate „imide“ the system as a credible actor. The text is based on the analytical premise that the EU is not a static entity modeled on a national unitary state or federation, but a dynamic political system. The current definition of Euroscepticism, however, is based on the notion of the EU having a static nature and the existence of the finality of European integration process, which significantly affects the EU political system’s ability to perform the basic functions of a functioning political system – in particular the function of evaluation and (re)formulation of policy objectives. The most important consequence of this approach is the inability of the EU to receive any critical feedback and work with it as a relevant political input.